2018
DOI: 10.1007/s00244-018-0580-4
|View full text |Cite
|
Sign up to set email alerts
|

Ecotype Variation in Trace Element Content of Hard Tissues in the European Roe Deer (Capreolus capreolus)

Abstract: Animals living in anthropogenic habitats bear a multitude of costs, which are directly or indirectly associated with human activities. Among others, an elevated exposure to environmental pollution can have negative consequences for wildlife populations. We examined the differences in the concentrations of trace elements between the field and forest ecotype of the European roe deer (Capreolus capreolus). Naturally, roe deer inhabited various types of woodlands (forest ecotype), but within the last century, they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 78 publications
3
16
0
Order By: Relevance
“…However, the concentration of this metal in the bones was higher in the samples from the wild deer and lower in the farmed deer in comparison with levels determined in samples from caribou living near a mine in Northern Alaska [ 39 ]. The bone Ba concentration was higher in the wild red deer and lower in the farmed animal group than the levels determined in roe deer from forest and field habitats of central Europe [ 20 , 40 ]. The concentrations of Cd and Pb in the bones of reindeer living in Karelia (Russia) were much higher than those reported in the present study [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the concentration of this metal in the bones was higher in the samples from the wild deer and lower in the farmed deer in comparison with levels determined in samples from caribou living near a mine in Northern Alaska [ 39 ]. The bone Ba concentration was higher in the wild red deer and lower in the farmed animal group than the levels determined in roe deer from forest and field habitats of central Europe [ 20 , 40 ]. The concentrations of Cd and Pb in the bones of reindeer living in Karelia (Russia) were much higher than those reported in the present study [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Large herbivores, e.g., roe deer ( Capreolus capreolus ), red deer ( Cervus elaphus ), reindeer ( Rangifer tarandus ), and moose ( Alces alces ) have been shown to be good bioindicator species in monitoring programs, which have been developed since 1980 in different countries in Central Europe and Scandinavia [ 19 ]. Furthermore, it has been shown that deer bone tissues can serve as environmental bioindicators [ 20 , 21 ], especially bones and teeth, which unlike antlers are not replaced every year and accumulate trace elements over years or decades [ 22 ]. In humans, for instance, the biological half-life of trace elements in bone tissue lasts up to 30 years, and their content in bones is up to 90% [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Both xenobiotics, Pb and Cd, enter living organisms via two major routes: enteral and respiratory [ 3 ], and due to their high mobility in the natural environment and strong tendency to accumulate, they undergo biomagnification in the food chain [ 4 ]. Game species spend their whole life in their natural habitats, and therefore, their tissues can be used as excellent indicators for the measurement of local pollution levels [ 5 , 6 , 7 , 8 , 9 ]. The transfer of elements from soil to plants and animals also depends on soil conditions, i.e., redox potential, pH or the content, of organic matter and plant physiology [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some plants tend to accumulate more pollutants [ 10 ] of which the consumption by an animal is a source of direct exposure to these compounds and their increased accumulation in animal tissues [ 7 ]. Toxic elements can accumulate in hard tissues, such as bones, teeth [ 7 , 8 ] and antlers [ 9 ], in hair [ 3 , 5 , 13 , 14 ] and in the parenchymal organs, such as the liver [ 4 , 15 , 16 ], muscles [ 6 , 17 ] and kidneys [ 4 , 18 ]. Red deer living in a given area have different access to essential trace elements and toxic elements, which is reflected in their different concentration in animal tissues [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of meat harvested in forests and fields can be a bioindicator of the level of environmental contamination. By monitoring the existence of animals, the place of harvesting and many other factors, the level of environmental pollution can be assessed [25][26][27][28]. Evaluation of the degree of bioaccumulation of lead and cadmium in the muscle tissue of animals, including roe and red deer, is a criterion for assessing the safety of such products for consumption.…”
Section: Introductionmentioning
confidence: 99%